2021
DOI: 10.3389/fped.2021.675022
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Hypoxia Changed the Colonization of the Gut Microbiota in Newborn Rats

Abstract: Background: Accumulating evidence suggests a connection between the gut microbiota and neonatal diseases. Hypoxia may play an important role in the intestinal lesions in neonates.Objective: This study aims to determine whether the gut microbiota differs between intrauterine hypoxic rats and healthy controls and to identify the factors that influence the changes in the gut microbiota.Methods: We constructed an intrauterine hypoxia model in rats and collected the intestinal contents of intrauterine hypoxic newbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…The dominant phyla in the gut microbiota were Firmicutes and Proteobacteria, followed by Actinomycetes and Bacteroidetes, according to the species composition analyses. This finding is in line with prior findings ( 27 - 29 ). The analysis of community composition on the 1st day showed that the ratio of Firmicutes/Bacteroidetes was the lowest in the Agonist1 group.…”
Section: Discussionsupporting
confidence: 94%
“…The dominant phyla in the gut microbiota were Firmicutes and Proteobacteria, followed by Actinomycetes and Bacteroidetes, according to the species composition analyses. This finding is in line with prior findings ( 27 - 29 ). The analysis of community composition on the 1st day showed that the ratio of Firmicutes/Bacteroidetes was the lowest in the Agonist1 group.…”
Section: Discussionsupporting
confidence: 94%
“…14 Our results show the fecal microbiota of neonatal rats to be characterized by high enrichment of Firmicutes and Proteobacteria but lacking in Bacteroidetes. Similar patterns have been observed in P7 rats 17 and newborn infants 18 and likely reflect the immature and developing nature of the infant microbiota. The diet switch from KD → ND was associated with numerous changes including a notable decrease in Streptococcus thermophilus.…”
Section: Discussionsupporting
confidence: 77%
“…It is interesting to note that serum IgG levels of these foals were lower than those of healthy foals despite the administration of good quality colostrum. Since hypoxic–ischemic insult can affect the intestinal tract [ 63 ], this could cause reduced efficiency of IgG intestinal absorption, as recently suggested [ 64 ]. Furthermore, there was a higher frequency of FPT in Group 2, despite medical intervention.…”
Section: Discussionmentioning
confidence: 99%